2016
DOI: 10.18632/oncotarget.8923
|View full text |Cite
|
Sign up to set email alerts
|

MnTnBuOE-2-PyP protects normal colorectal fibroblasts from radiation damage and simultaneously enhances radio/chemotherapeutic killing of colorectal cancer cells

Abstract: Manganese porphyrins have been shown to be potent radioprotectors in a variety of cancer models. However, the mechanism as to how these porphyrins protect normal tissues from radiation damage still remains largely unknown. In the current study, we determine the effects of the manganese porphyrin, MnTnBuOE-2-PyP, on primary colorectal fibroblasts exposed to irradiation. We found that 2 Gy of radiation enhances the fibroblasts' ability to contract a collagen matrix, increases cell size and promotes cellular sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…In our previously published study, we reported that MnTnBuOE-2-PyP, a sister compound of MnTE-2-PyP, can protect colorectal fibroblasts from 2 Gy radiation-induced damage (11). For the current study, we investigated the underlying mechanism of MnTE-2-PyP in protecting normal tissue from radiation-induced fibrosis and senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previously published study, we reported that MnTnBuOE-2-PyP, a sister compound of MnTE-2-PyP, can protect colorectal fibroblasts from 2 Gy radiation-induced damage (11). For the current study, we investigated the underlying mechanism of MnTE-2-PyP in protecting normal tissue from radiation-induced fibrosis and senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported studies have shown that MnTE-2-PyP can protect from radiation-induced external tissue damage in rats (9), without protecting the tumor (10). MnTnBuOE-2-PyP, a sister compound of MnTE-2-PyP, has been shown to protect normal colorectal fibroblast cells, while simultaneously enhancing the cytotoxic effects of radiation or chemotherapeutic agents on colorectal cancer cells (11). Understanding the mechanism by which a compound works is helpful for successful clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the environment, MnPs can act in either an antioxidant or pro-oxidant capacity. MnBuOE has been shown to sensitize tumor cells to chemotherapy and radiotherapy while protecting normal tissue by modulating tissue redox [17,21].…”
Section: Introductionmentioning
confidence: 99%
“…Cationic manganese-(Mn-) substituted N-pyridylporphyrins (MnPs) were initially developed as powerful SOD mimic, and MnPs, which regulate intracellular redox environment, have reached the stage of clinical application [12]. It has been reported that intraperitoneal injection of MnTE-2-PyP (BMX-010, AEOL10113) during radiotherapy performed on the lower abdomen of rats significantly reduced radiation damage to normal tissues such as the skin, prostate, and testis [13], while a similar compound, MnTnBuOE-2-PyP (BMX-001), protected normal tissue effectively while enhancing radiotherapy and chemotherapy treatment in colorectal cancer [14]. It is noteworthy that MnPs have been reported to improve epidermal wound healing.…”
Section: Introductionmentioning
confidence: 99%